Developmental effects in social facilitation and in being a model - Newman, Alexander; Dickstein, Renie; Gargan, Michelle (1978)
The present study explored audience effects as a function of (a) age of performer and (b) role as model or performer. Five-, eight-, and 11?year-old children (N # 72 boys and girls) performed seven acquisition trials of the WISC Object Assembly item #3 (FACE) and seven trials of Object Assembly #4 (AUTO) alone or in the presence of a peer who was a confederate of the E. In the audience conditions, the performer was told in the model condition that the observer would learn by watching him perform, or in the neutral audience condition that the observer was simply waiting for the E to return. Compared to the alone condition, the neutral audience produced a negative audience effect in 11-year-olds but not in the five- and eight-year-olds. For all ages, the model group was consistently superior to the alone and neutral audience conditions. Implications for social-learning theories of development are discussed.